Psychosis, spirit possession and child sexual abuse - Da Breo, Hazel, author.
1 online resource
Keywords: "This distinctive volume examines the psychological claims of spirit possession and psychosis as they are linked to child sexual abuse, intimate partner violence, and poor mental health. In the context of both clinical complaints and community-based determinants, this book uses Jungian and Fanonian theory, political history, and case study analysis to explore the systems at work in projecting internalized traumas of colonialism and personal powerlessness onto a scapegoated demonic presence affecting victims/survivors of sexual violence. It focuses on populations of the global south but is relevant to victims of oppression worldwide, considering the personal unconscious and cultural complexes that influence a sense of being overtaken and controlled by supernatural or intrapsychic forces, or a desire to be. Psychosis, Spirit Possession and Child Sexual Abuse offers an alternative framework for understanding mental processes that lead to symptoms such as auditory or visual hallucinations that often get misdiagnosed and mistreated. This is important reading for practitioners and scholars of depth psychology and is of keen interest to academics in the fields of foreign and cultural studies, as well as students and researchers in sociology, religion or anthropology"--